Physiological responses of cultured bovine granulosa cells to elevated temperatures under low and high oxygen in the presence of different concentrations of melatonin - Zeebaree, Bayar K.; Kwong, Wing Y.; Mann, George E.; Gutierrez, Carlos G.; Sinclair, Kevin D. (Elsevier, 2018)
Our understanding of the effects of temperature on granulosa cell (GC) physiology is primarily limited to in vitro studies conducted under atmospheric (approx 20% O2) conditions. In the current series of factorial experiments we identify important effects of O2 level (i.e. 5% vs 20% O2) on GC viability and steroidogenesis, and go onto report effects of standard (37.5°C) vs high (40.0°C) temperatures under more physiologically representative (i.e. 5%) O2 levels in the presence of different levels of melatonin (0, 20, 200 and 2000 pg/mL); a potent free-radical scavenger and abundant molecule within the ovarian follicle. Cells aspirated from antral (4 to 6 mm) follicles were cultured in fibronectin-coated wells using serum-free M199 for up to 144 h. At 37.5 C viable cell number was enhanced and luteinization reduced under 5 vs 20% O2. Oxygen level interacted (P<0.001) with time in culture to affect aromatase activity and cell estradiol (E2) production (pg/mL/105 cells). These decreased between 48 and 96 h for both O2 levels but increased again by 144 h for cells cultured under 5% but not 20% O2. Progesterone (P4) concentration (ng/mL/105 cells) was greater (P<0.001) under 20 vs 5% O2 at 96 and 144 h. Cell number increased (P<0.01) with time in culture under 5% O2 irrespective of temperature. However, higher doses of melatonin increased viable cell number at 40.0°C but reduced viable cell number at 37.5°C (P=0.004). Melatonin also reduced (P<0.001) ROS generation at both O2 levels across all concentrations. E2 increased with time in culture at both temperatures under 5% O2, however P4 declined between 96 to 144 h at 40.0 but not 37.5°C. Furthermore, melatonin interacted (P<0.001) with temperature in a dose dependent manner to increase P4 at 37.5°C but to reduce P4 at 40.0°C. Transcript expression for HSD3B1 paralleled temporal changes in P4 production, and those for HBA were greater at 5% than 20% O2, suggesting that hemoglobin synthesis is responsive to changes in O2 level. In conclusion, 5% O2 enhances GC proliferation and reduces luteinization. Elevated temperatures under 5% O2 reduce GC proliferation and P4 production. Melatonin reduces ROS generation irrespective of O2 level and temperature, but interacts with temperature in a dose dependent manner to influence GC proliferation and luteinization.